Sense of purpose in life, cognitive function, and the phenomenology of autobiographical memory. Issue 9 (21st October 2021) - Sutin, Angelina R.; Luchetti, Martina; Aschwanden, Damaris; Stephan, Yannick; Terracciano, Antonio
ABSTRACT: There are individual differences in the phenomenological re-experiencing of autobiographical memories. We examine whether sense of purpose in life and cognitive function are associated with the phenomenology of a recent memory related to the coronavirus pandemic. Participants reported on their sense purpose and completed tasks that measured processing speed and visuospatial ability before the pandemic in January-February 2020 and subsequently retrieved and rated a memory related to the pandemic in July 2020 ( N =796; M age =58.05, SD =14.14, range 19-85). Participants with a greater sense of purpose reported memories that were more phenomenologically rich (e.g., more vivid, coherent, accessible), whereas cognitive function was primarily related to greater perceived accessibility of the memory but not to most other aspects of phenomenology. The pattern of associations was similar when accounting for depressive symptoms, and none of the associations was moderated by age. The present research suggests that individuals with a higher sense of purpose in life have autobiographical memories with richer phenomenology. To the extent that memories function to sustain well-being, social connections, and cognitive health, rich phenomenology may be one pathway through which purpose leads to these better outcomes.